Uncle Jack and the Bakonzi Tree - Cadwallader, Jane (Italy ELI - Young Readers, 2009)
A nail biting adventure in the Rwandan rainforest with Uncle Jack, Jim, Daisy and May (and of course Grumpy the dog!). Can they save the life of King Kambogo?
Picture dictionary, games and activities.
Keywords: Adventure; Classroom activities; Story; Elementary level